Effect of Different Luting Protocols on the Bond Strength of Fiber-Reinforced CAD/CAM Blocks - Buyukates, Irem; Garoushi, Sufuan; Vallittu, Pekka K; Uctasli, Sadullah; Lassila, Lippo (MDPI, 2026)
The aim was to evaluate the shear-bond strength (SBS) of experimental short fiber-reinforced CAD/CAM composites (SFRC-CAD) and commercial CAD/CAM composites (Cerasmart 270) to different luting resin composites before and after hydrothermal aging. Discs (2 mm) obtained from SFRC-CAD and Cerasmart 270 were air-particle abraded and treated with a primer (G-CEM One Enhancing Primer) with or without universal adhesive (G2 Bond). A fiber-reinforced flowable composite (everX Flow) and a self-adhesive resin cement (G-CEM One) were used as luting materials under direct or indirect curing conditions. Thirty-two experimental groups were determined based on restorative material, bonding protocol, luting resin, curing technique, and aging procedure (n = 8/group). SBS was measured after 24 h of water storage or following hydrothermal aging. Data were analyzed using nonparametric statistical tests (p < 0.05). No statistically significant differences in SBS were observed between everX Flow and G-CEM One regardless of the bond application (p > 0.05). SFRC-CAD bonded with everX Flow and universal adhesive demonstrated significantly higher SBS than the corresponding Cerasmart groups (p < 0.05), whereas no significant differences were observed between comparable groups when G-CEM One was used. Failure mode analysis showed predominantly adhesive and mixed failures, with no cohesive failures within SFRC-CAD. Overall, the everX Flow proved to be an effective luting material, indicating that this material may be suitable for luting CAD/CAM indirect restorations.